2012
DOI: 10.1161/circresaha.111.243170
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Myocardial Diseases

Abstract: Inflammatory processes underlie a broad spectrum of conditions that injure the heart muscle and cause both structural and functional deficits. In this article, we address current knowledge regarding 4 common forms of myocardial inflammation: myocardial ischemia and reperfusion, sepsis, viral myocarditis, and immune rejection. Each of these pathological states has its own unique features in pathogenesis and disease evolution, but all reflect inflammatory mechanisms that are partially shared. From the point of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
167
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(172 citation statements)
references
References 211 publications
(227 reference statements)
2
167
1
2
Order By: Relevance
“…Inflammatory processes are involved in many conditions that injure the myocardium and cause both structural and functional defects in the heart (15,16), and glucocorticoids have welldocumented anti-inflammatory actions. Examination of the genes dysregulated in the hearts of the cardioGRKO mice by both IPA and GO revealed a prominent association with the immune response and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes are involved in many conditions that injure the myocardium and cause both structural and functional defects in the heart (15,16), and glucocorticoids have welldocumented anti-inflammatory actions. Examination of the genes dysregulated in the hearts of the cardioGRKO mice by both IPA and GO revealed a prominent association with the immune response and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…27) Previous investigations have demonstrated that interventions targeted for infl ammatory responses improve MI. 1,2) Among numerous infl ammatory mediators involved, IL-1β is an early and prominent mediator for inflammatory responses in MI.…”
Section: Nlrp3 Inflammasome and Myocardial Infarction (Mi)mentioning
confidence: 99%
“…It is known that inflammation plays an important role in the pathophysiology of I/R injury 4, 5, 6. Myocardial I/R injury‐induced inflammatory responses are typically associated with increased cytokines secretion, upregulated expression of cell adhesion molecules, and enhanced neutrophil infiltration and microvascular permeability 7.…”
Section: Introductionmentioning
confidence: 99%